Understanding Payment for Forest Environmental Services in Vietnam in times of Covid-19: Research methods and guidelines - Pham Thu Thuy; Hoàng, T.L.; Dương, T.B.N.; Lê, T.T.T.; Trần Ngọc, M.H. (Center for International Forestry Research, 2022)
The Government of Vietnam and donors have launched numerous programmes and policies to support vulnerable communities’ livelihoods, nutrition and agency and to cope COVID-19. Payment for Forest Environmental Services (PFES) has a potential role in contributing to the government policy mix to address Covid-19 impacts.